Antibacterial and antibiofilm activities of bay [Syzygium polyanthum (Wight) Walp.] leaf extract against planktonic and biofilm growth of Listeria monocytogenes - Mohd Daud, Ili Syuhada (2019)
Adhesion of microorganism or biofilm formation to food contact surface can become a source of microbial contamination and give major implication in food industries. Moreover, interest has recently grown in discovery of natural antimicrobial agents such as plant extract. The aim of this study was to investigate the antibacterial and antibiofilm activity of bay [Syzygium polyanthum (Wight) Walp.] leaf extract against planktonic and biofilm growth of Listeria monocytogenes strains. In this study, 9 strains of L. monocytogenes isolated from vegetables and one standard L. monocytogenes ATCC®19112™ were used. The standard strain (ATCC®19112™) and the local isolates were used to study the difference of antibacterial resistance towards bay [S. polyanthum (Wight) Walp.] leaf extract. Antibacterial activity of bay [S. polyanthum (Wight) Walp.] leaf extract against planktonic L. monocytogenes strains were investigated using the methods described by Clinical and Laboratory Standards Institute (CLSI) in term of disc diffusion, minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC) and time-kill curve analysis. Whereas in vitro biofilm formation ability of L. monocytogenes and antibiofilm activity of the extract against L. monocytogenes biofilms were evaluated in pre-sterilized 96-well microplate using 2,3-bis(2-methoxy-4-nitro-5-sulfophenyl)-5-[(phenylamino) carbonyl]-2H-tetrazolium-hydroxide (XTT) reduction assay. Moreover, the effect of bay [S. polyanthum (Wight) Walp.] leaf extract on L. monocytogenes ATCC®19112™ biofilms were visually observed using scanning electron microscopy (SEM). Finally, the effects of ethanolic extract of bay [S. polyanthum (Wight) Walp.] leaf were tested on bean sprout (Vigna radiata) that has been spiked with approximately 106-108 CFU/mL of L. monocytogenes. The results showed that all tested L. monocytogenes strains were susceptible to bay [S. polyanthum (Wight) Walp.] leaf extract with clear zone ranging from 6.50 mm to 8.00 mm for ethanolic extract and 6.50 mm to 7.50 mm for methanolic extract. The extract can inhibit the growth of L. monocytogenes with MICs ranging from 0.31 to 1.25 mg/mL. The extract also can kill completely the L. monocytogenes strains with MBCs ranging from 0.63 to 5.00 mg/mL. Based on time-kill curves established at 0× MIC, 1/2× MIC, 1× MIC, 2× MIC and 4× MIC of bay [S.polyanthum (Wight) Walp.] leaf extract, the bactericidal endpoints for tested L. monocytogenes was fast acting from 0.63 to 5.00 mg/mL. Furthermore, four L. monocytogenes strains; 58a, 58b, 90g and ATCC®19112™ were classified as strong biofilm producer in vitro, with optical densities (ODs) ranging from 0.66 to 1.77, which were greater than optical density of negative control (ODc) ranging from 0.09 to 0.12. The sessile minimum inhibitory concentrations (SMICs) for both ethanolic and methanolic extract against the strong biofilm producer ranged from 0.63 to 2.50 mg/mL and 1.25 to 5.00 mg/mL, respectively. The minimal biofilm eradication concentrations (MBECs) of both ethanolic and methanolic leaf extract were varied from 5.00 mg/mL to >5.00 mg/mL. From the observation using SEM, most of the L. monocytogenes vegetative cells and biofilms were noticeably disrupted after treated with bay [S. polyanthum (Wight) Walp.] leaf extract at concentration of 5.00 mg/mL. In the simulation study, generally the significant reduction of natural microflora in bean sprout (Vigna radiata) spiked with L. monocytogenes after treated with bay [S. polyanthum (Wight) Walp.] leaf extract was at concentration of 0.05% for 5 min exposure time. Overall, the results showed that bay [S. polyanthum (Wight) Walp.] leaf extract possess strong antibacterial and antibiofilm activity against L. monocytogenes. In conclusion, bay [S. polyanthum (Wight) Walp.] leaf extract can be developed as a natural food sanitizer or preservative.